Epithelium-Innate Immune Cell Axis in Mucosal Responses to SIV - Shang, L. (Mucosal Immunol, 2016)
In the SIV-rhesus macaque model of HIV-1 transmission to women, one hallmark of the mucosal response to exposure to high doses of SIV is CD4 T cell recruitment that fuels local virus expansion in early infection. In this study, we systematically analyzed the cellular events and chemoattractant profiles in cervical tissues that precede CD4 T cell recruitment. We show that vaginal exposure to the SIV inoculum rapidly induces chemokine expression in cervical epithelium including CCL3, CCL20, and CXCL8. The chemokine expression is associated with early recruitment of macrophages and plasmacytoid dendritic cells that are co-clustered underneath the cervical epithelium. Production of chemokines CCL3 and CXCL8 by these cells in turn generates a chemokine gradient that is spatially correlated with the recruitment of CD4 T cells. We further show that the protection of SIVmac239Δnef vaccination against vaginal challenge is correlated with the absence of this epithelium-innate immune cell-CD4 T cell axis response in the cervical mucosa. Our results reveal a critical role for cervical epithelium in initiating early mucosal responses to vaginal infection, highlight an important role for macrophages in target cell recruitment and provide further evidence of a paradoxical dampening effect of a protective vaccine on these early mucosal responses.